Tunable optical frequency comb from a compact and robust Er:fiber laser. (2020) - Zhu, Zhiwei; Liu, Yang; Luo, Daping; Gu, Chenglin; Zhou, Lian; Xie, Gehui; Deng, Zejiang; Li, Wenxue
Abstract : We report on a compact and robust self-referenced optical frequency comb with a tunable repetition rate, generated by an all-polarization-maintaining (PM) mode-locked Er-doped fiber laser. The spacing between comb teeth can be tuned above 300 kHz at a repetition rate of 101 MHz. The repetition rate and the carrier–envelope offset of the laser are stabilized separately, and the relative residual phase noises are determined to be 336 [STIX]x03BCrad and 713 mrad (1 Hz–1 MHz). The accurate frequency characteristics and the stable structure show great potential for the use of such a comb in applications of precision measurements.